Protocol to study oxygen dynamics in the in vivo mouse brain using bioluminescence microscopy - Antonios Asiminas; Ryszard S. Gomolka; Stefanie Gregoriades; Hajime Hirase; Maiken Nedergaard; Felix R.M. Beinlich (STAR Protocols)
Summary: Bioluminescence imaging (BLI) relies on the biochemical reaction between substrate and enzyme that triggers light emission upon convergence. Here, we present a protocol to study molecular oxygen dynamics in the in vivo mouse brain using the oxygen-dependent reaction between luciferase and its substrate. We describe steps for acute craniotomy, viral transfection, substrate administration, imaging, and analysis of hypoxic pockets. This protocol offers superior spatiotemporal properties compared to established approaches like electrodes and phosphorescence.For complete details on the use and execution of this protocol, please refer to Beinlich et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.